Women's Empowerment and Gender Equality in Downstream Coffee: Through the Women's Empowerment in Agriculture Index (WEAI) Framework - Ninda Novita; Putra Irwandi; Fayi Afifah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Women have a strategic role in the development of agribusiness, especially in the downstream coffee sector. The Coffee Village Center in Nagari Koto Tuo, Tanah Datar Regency is a unique area because the black coffee business is managed by women for generations in the matrilineal kinship system. This study aims to analyze the level of women's empowerment and gender equality in black coffee entrepreneurial households using the Women's Empowerment in Agriculture Index (WEAI) framework. The research method used a quantitative approach with census techniques on 160 women entrepreneurs. Data were collected through structured interviews using questionnaires and analyzed using 5 indicators of Domains of Empowerment (5DE) and Gender Parity Index (GPI). The results showed that the level of women's empowerment had a score of 5DE of 0.59 which was included in the category of quite empowered. Women have played a role in production decision-making, income management, and social activities, but are still limited to formal credit access, asset ownership, and workload. Meanwhile, a GPI value of 0.51 indicates that gender equality in households has not been fully achieved. Overall, the WEAI value of 0.834 indicates that the level of women's empowerment is in the good category, although there is still a latent gender gap. These findings confirm that the increase in women's empowerment has not been fully followed by gender equality in entrepreneurial households.